(untitled) (Journal of Engineering and Health Sciences, 2020)
Pigment-producing microorganisms have become a main focus due to the search of food-grade microbial pigments for natural food colourant industry. Therefore, this study aimed to isolate and genetically identify bacteria including pigment-producing bacterial strains associated with the tentacles of Holothuria (Lessonothuria) pardalis (Selenka 1867) from Pulau Tinggi, Johor. Morphological characteristics of bacteria based on Gram staining were observed using a digital compound microscope. Partial 16S ribosomal RNA (rRNA) gene sequencing was also incorporated to support the morphological approach. A number of six partial gene sequences of non-protein coding 16S rRNA were obtained and the Basic Local Alignment Search Tool (BLAST) analysis suggested the presence of three known bacteria species from the genera of Pseudomonas, Chryseobacterium and Klebsiella. The neighbourhood-joining method and Maximum Likelihood method used in the phylogenetic analysis supported the identification and classification of the bacteria species. Among the bacterial isolates, only strain B14 identified as Chryseobacterium sp. produced pigment i.e. orange pigment. The highest point of cell density of Chryseobacterium sp. was recorded at 16 hours. However, further analysis is needed to confirm the pigment characterisation and the potential of this pigment to be exploited as natural colourant in the food industry.